International lower secondary science 2 - Leng, Ho Peck (Marshall Cavendish Education, 1999)
"International Lower Secondary Science 2" is a comprehensive science textbook designed for lower secondary students, typically around the ages of 12-14. It covers key scientific concepts and topics across various disciplines, including biology, chemistry, and physics, following an international curriculum. The book focuses on building foundational scientific knowledge and skills, encouraging critical thinking, problem-solving, and practical application of scientific principles through experiments and activities. Each chapter is structured to facilitate learning with clear explanations, diagrams, and assessments to track student progress and understanding.